Sodba o sodnem svetu - Zalar, Aleš (Podjetje in delo, 2024)
Within the procedure of amending the chapter on judiciary of the Slovenian Constitution, the most professional polemic was triggered by the suggested new Article 131 of the Constitution, with the following effects: the overall number of the members of the Judicial Council would be increased, the President of the Republic would no longer nominate the candidates for the position of member of Judicial Council, being elected by the National Assembly, and the National Assembly would elect members of the Judicial Council by two thirds majority of votes of the present members of the National Assembly. The author critically deals with objections of the Judicial Council against the mentioned constitutional changes and analyses the argumentation of the Judicial Council and of the Expert Group of the Constitutional Commission considering recognised international legal standards and recommendations, as well as constitutional principle of separation of powers.